2005
DOI: 10.7863/jum.2005.24.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Sonographic Imaging for Periradicular Injections in the Lumbar Spine

Abstract: Objective. We conducted this study to develop a sonographically guided approach to the spinal nerve of the lumbar spine and to assess its feasibility and accuracy by means of computed tomography (CT). Methods. Fifty sonographically guided approaches at 5 levels (L1-S1) were performed on 5 embalmed cadavers, which were positioned prone. The spinal nerves of the lumbar spine were shown under sonographic guidance. In 1 cadaver, the most lateral aspect of the roof of the intervertebral foramen was defined as a ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 15 publications
0
61
0
11
Order By: Relevance
“…The currently established technique for sonographyguided lumbar nerve root instillation as proposed by Galiano et al 14 consists of an axial approach toward the respective spinal level. While this technique is optimally suited for lumbar zygapophyseal joint injections because of the ideal visualiza- tion of the joint space in a transverse scanning plane, the authors of this article reported difficulties with nerve root injection in the upper lumbar segments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The currently established technique for sonographyguided lumbar nerve root instillation as proposed by Galiano et al 14 consists of an axial approach toward the respective spinal level. While this technique is optimally suited for lumbar zygapophyseal joint injections because of the ideal visualiza- tion of the joint space in a transverse scanning plane, the authors of this article reported difficulties with nerve root injection in the upper lumbar segments.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] US guidance for spinal injection is a recent development but, according to the literature, seems promising. [11][12][13][14][15][16][17][18][19][20] US has proved sufficiently reliable and accurate in the demonstration of lumbar paravertebral anatomy, [11][12][13][14]21 and the feasibility of US-guided injection therapy at the spine has also been demonstrated in several studies. [11][12][13][14][15][16][17][18][19][20] Although US is considered reliable for different injection procedures of the lumbar spine, [11][12][13][14] some disadvantages of the currently proposed methods-particularly in the upper lumbar spine-have been discussed.…”
mentioning
confidence: 99%
“…In the past, ultrasound (US) has been demonstrated to facilitate the localization and imaging of peripheral nerves, spinal nerve roots and also bony parts of the spine such as facet joints. US-guided approaches tailored for spinal interventions are already available, but only proven for their topographic feasibility [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Beginning in 2004, the reports of US guidance in facet procedures in the cervical [31, 47, 50, 65 • , 66-69] and lumbar spine [18,32,70] were described in the literature. Comprehensive review of the literature shows a higher number of quality studies evaluating the role of US in lumbar facetrelated procedures (Table 1).…”
Section: Ultrasound Guided Lumbar Facet Injectionsmentioning
confidence: 99%
“…Galiano et al [32] described a feasibility and accuracy study of US guidance in the lumbar spine using a transforaminal approach with subsequent CT imaging. Fifty USguided approaches at five levels (L1-S1) were performed on five embalmed cadavers, and the Pearson correlation coefficient was 0.99 (P \ .001) between sonography and CT.…”
Section: Ultrasound-guided Lumbar Epidural Injectionsmentioning
confidence: 99%